Influence of infection route and virulence factors on colonization of solid tumors bySalmonella entericaserovar Typhimurium - Katja Crull; Dirk Bumann; Siegfried Weiß (2011)
Administration of facultative anaerobic bacteria such as Salmonella enterica serovar Typhimurium as anticancer treatment holds a great therapeutic potential. Here, we tested different routes of application of S. typhimurium with regard to tumor colonization and therapeutic efficacy. No differences between intravenous and intraperitoneal infection were observed, often leading to a complete tumor clearance. In contrast, after oral application, tumor colonization was inefficient and delayed. No therapeutic effect was observed under such conditions. We also showed that tumor invasion and colonization were independent of functional Salmonella pathogenicity island (SPI) 1 and SPI 2. Furthermore, tumor invasion and colonization did not require bacterial motility or chemotactic responsiveness. The distribution of the bacteria within the tumor was independent of such functions.